Potential lipid-lowering effects of Ulmus macrocarpa Hance extract in adults with untreated high low-density lipoprotein cholesterol concentrations: A randomized double-blind placebo-controlled trial - Lee, Ye Li; Lee, Sang Yeoup (Frontiers in Medicine, 2022)
Introduction Ulmus macrocarpa Hance extract (UME) has demonstrated an antilipidemic effect via upregulation of the adenosine monophosphate-activated protein kinase pathway and regulation of lipid metabolism in both laboratory and animal studies. Therefore, we examined the effects and safety of UME on plasma lipids in adults with untreated high, low-density lipoprotein cholesterol (LDL-C) concentrations. Materials and methods In the current double-blind placebo-controlled randomized clinical trial, 80 patients with untreated high LDL-C concentrations (130–190 mg/dl) were randomly allocated to either the “UME group” (received 500 mg UME as two capsules per day) or the “Placebo group” (received placebo containing cornstarch as two capsules per day) for 12 weeks. The primary outcome was the change in LDL-C concentration within the 12-week treatment period; secondary outcomes included changes in total cholesterol (TC), triglyceride, high-density lipoprotein cholesterol, apolipoprotein A1, and apolipoprotein B (ApoB) concentrations. Results UME over 12 weeks led to a greater decrease in LDL-C, TC, and ApoB concentrations than did the placebo as follows: by 18.1 mg/dl (P < 0.001); 23.3 mg/dl (P < 0.001); 9.3 mg/dl (P = 0.018), respectively. When LDL-C, TC, and ApoB concentrations were expressed as a lsmeans percentage of the baseline concentration, they after 12 weeks of UME had greater % differences compared to the placebo as follows: by 11.9% (P < 0.001); 10.0% (P < 0.001); 8.6% (P < 0.05), respectively. However, no significant inter- and intra-group changes in liver enzyme, free fatty acid, anti-inflammatory marker, and fasting glucose concentrations were observed. None of the participants experienced notable adverse events. Discussion UME causes a significant improvement in lipid profiles in adults with untreated high LDL-C concentrations. Clinical trial registration [www.clinicaltrials.gov/], identifier [NCT03773315].